2012
DOI: 10.1097/pas.0b013e318235ee03
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Minichromosome Maintenance MCM6 Protein in Meningiomas is Strongly Correlated With Histologic Grade and Clinical Outcome

Abstract: The 2007 World Health Organization histologic grading of meningiomas is associated with recurrence and clinical outcome. However, distinction of grade I from grade II (atypical) meningiomas can be challenging. In the World Health Organization classification, there are 4 parameters on the basis of which grade II status can be determined: mitotic rate, cytoarchitectural features, brain invasion, and/or histologic subtype. Furthermore, this classification fails to detect grade I recurrent meningiomas, for which o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 49 publications
2
35
1
2
Order By: Relevance
“…The minichromosome maintenance protein (MCM) family is implicated in the control of eukaryotic genome replication and proves to be useful markers for tumor proliferation [24]. Several studies demonstrated overexpression of MCM6 also predicts poor survival in patients with several types of cancer, including HCC [31][32][33][34]. Future studies should attempt to clarify the underlying mechanism of GTSE1 together with minichromosome-related protein-mediated DNA replication and cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The minichromosome maintenance protein (MCM) family is implicated in the control of eukaryotic genome replication and proves to be useful markers for tumor proliferation [24]. Several studies demonstrated overexpression of MCM6 also predicts poor survival in patients with several types of cancer, including HCC [31][32][33][34]. Future studies should attempt to clarify the underlying mechanism of GTSE1 together with minichromosome-related protein-mediated DNA replication and cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Martin et al, in a systematic review with meta-analysis, concluded Ki-67 to be a bad prognosis marker for survival in 15 out of 37 studies [1]. Among other proliferation markers, the mini-chromosome maintenance (MCM) proteins -key proteins in the initiation of DNA synthesis and DNA replication -were shown to be associated with histological grades in various neoplastic processes [4]. In lung cancer, few studies have evaluated the prognostic value of the MCMs proteins, including MCM2, MCM4, and MCM7 [2,5,6].…”
Section: Introductionmentioning
confidence: 96%
“…13 Recent reports have showed that increased expression of MCM family proteins are related to several tumors including HCC. [14][15][16][17] For example, detection of stool MCM can be used for detection of colorectal cancer, 14 MCM5 is used in diagnosis of pancreaticobiliary malignancy in bile aspirates, 15 expression of MCM6 protein in meningiomas is strongly correlated with histological grade and clinical outcome, 16 MCM7 expression also predicts postoperative prognosis for HCC. 17 Our previous results also indicated that MCM6 is overexpressed in HCC tissues.…”
Section: Introductionmentioning
confidence: 99%